Our Present Misfortune: Games and the Post-bureaucratic Colonization of Contingency - Malaby, Thomas M (Logos, 2020)
Anthropology is turning toward a new engagement with a central question of Weber: how do people come to understand the distribution of fortune in the world? Our discipline’s recent examination of the uses of the past prompts us to ask how stances toward the future are both the product of cultural logics and the target of institutional interests. In this article, I trace the engagement with contingency in anthropology and social thought, and then compare the nonchalant stance toward the future found in Greek society with the different disposition of individual gaming mastery in the digital domain, such as in Second Life, but also in the longest-running Greek state-sponsored game: Pro-Po. These examples illustrate how games are increasingly the sites for institutional efforts both to appropriate creativity and to generate distinctive subjectivities.